Effectiveness of Slow Stroke Back Massage Using Ylang Essential Oil on Reducing Blood Pressure Hypertension Patients - Normaliyanti; Muhammad Riduansyah; Eirene Eunike Meidiana Gaghauna (Journal of Advances in Medicine and Pharmaceutical Sciences, 2022)
Hypertension is a chronic condition when the blood pressure on the increase the blood vessels. Hypertension cases in Banjar Regency in 2021 were 15,083 cases. One of the non-pharmacological therapies that can reduce blood pressure is slow stroke back massage using ylang essential oil. Slow stroke back massage using ylang essential oil can have an effect on relaxation, blood circulation and is also useful as a lowering of blood pressure. The purpose of this study was to determine the effectiveness of slow stroke back massage using ylang essential oil on reducing blood pressure in patients with hypertension in Paku Alam village. This research method uses a one group pretest posttest design. The population in this study were patients with hypertension in the village of Paku Alam RT.03. The number of samples in this study were 10 people taken by purposive sampling technique. Data were analyzed using paired t-test. The research instrument uses Standard Operating Procedures (SOP) and observation sheets. The results of this study found that blood pressure decreased after giving slow stroke back massage using ylang essential oil. The results of the analysis test obtained that the systolic p value = 0.00 < (0.05) and the diastolic p value = 0.004 < (0.05) . So it can be concluded that there is an effectiveness of slow stroke back massage using ylang ylang essential oil on reducing blood pressure in patients with hypertension in Paku Alam Village.